2007
DOI: 10.1111/j.1440-1630.2007.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and challenges of supervising occupational therapy fieldwork students: Supervisors’ perspectives

Abstract: Background/aim: Increased enrolments in occupational therapy education programs, together with changes in the employment patterns of practising occupational therapists, have resulted in a crisis in fieldwork education in Australia.This study aimed to investigate fieldwork supervisors' perspectives regarding the benefits and challenges of providing fieldwork placements, explore the potential link between providing student placements and later workforce recruitment, and document currently employed models of fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 19 publications
5
67
0
2
Order By: Relevance
“…Therefore, identifying that all of our interview respondents had previous experience with other student-educator configurations is unsurprising. Likewise, our findings were consistent with previous literature, as roughly two-thirds of all fieldwork supervision was one-to-one (Thomas et al, 2007). Of interest is that the remaining onethird consisted of more than one therapist sharing the responsibility for the student.…”
Section: Interview Themessupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, identifying that all of our interview respondents had previous experience with other student-educator configurations is unsurprising. Likewise, our findings were consistent with previous literature, as roughly two-thirds of all fieldwork supervision was one-to-one (Thomas et al, 2007). Of interest is that the remaining onethird consisted of more than one therapist sharing the responsibility for the student.…”
Section: Interview Themessupporting
confidence: 82%
“…Bassett and Lloyd (2001) asserted that lack of resources and high caseloads lead to time constraints and greater stress for fieldwork supervisors. Moreover, the majority (n =103) of the fieldwork educators also indicated that time constraints made supervising fieldwork students either moderately or very challenging (Thomas et al, 2007). Three interviewees indicated that time is perpetually at a premium, and the additional commitment of time to supervising an occupational therapy student's fieldwork experience is often a barrier to maintaining optimal performance both as an educator to the occupational therapy student and as a practitioner for existing patients.…”
Section: Interview Themesmentioning
confidence: 99%
See 2 more Smart Citations
“…While much has been reported in the literature on the clinical education process 6 , the clinical educator's role and responsibilities 7 , clinical educator's preparedness 4,5,8 , and the benefits and challenges of clinical education 9,10 , very little has been published about the ethical responsibilities and issues associated with clinical education in occupational therapy. In the context of this paper the term 'clinical education' has been favoured over the term 'clinical supervision' as literature suggests the clinical or professional supervision is a process of professional development appropriate to qualified professionals while clinical education is the process of learning that applies to students as they gain clinical competencies from clinical experience [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%